3-TIERS MAINTENANCE STRATEGY FOR PROCESS EQUIPMENT - ISMAIL, IZYANI (2012)
In today's world of industries, companies must optimise every possible advantage to stand side by side with the other competitors. One of the ways is to increase the production performance while reducing the operational costs. Cost reduction can be achieved by managing assets where the life cycle of assets comes in hand with the aim of extending the life of those assets. In order to manage an asset, the maintenance of an asset must be planned and scheduled. It can be a challenging task where it gives a critical impact to the performance and overall equipment effectiveness ofthe assets. In order to optimise the overall equipment effectiveness and the cost of maintenance, it is important to select the best maintenance policy. However, most companies consider only one maintenance strategy in real implementation. Most ofthem involve in quantitative risk assessment which requires a detail data and it only focuses on particular equipment type. The objective of this study is to develop a qualitative framework for 3-tiers maintenance strategy that can easily be implemented in the process plant with respect to their condition and environment for all types of equipment. In order to achieve this objective, five steps have been developed; assessing the equipment, assessing its failure, choosing the suitable maintenance strategies, applying the maintenance strategies chosen and last but not least validation of the framework developed. A case study has been conducted in polyethylene plant where all the assets have been evaluated in terms of frequency of failure and severity of the impact where it covers economic, health, safety and environmental aspect. The results showed that by implementing this 3-tiers maintenance strategy, there are improvements in the reliability of equipment. This study will be an aid to the industries nowadays in implementing the suitable maintenance strategies chosen by their criticality in order to increase reliability whilst reducing labour workload and energy consumption.